2017
DOI: 10.18544/pedm-23.02.0078
|View full text |Cite
|
Sign up to set email alerts
|

Direction of change in the somatic development in children and adolescents with type 1 diabetes

Abstract: Changes in body build in patients with diabetes type 1 are associated with chronological age, duration of disease and metabolic control. It has been observed that the increase of weight and waist circumference concern girls. Patients with overweight and obesity represent a risk of early development of complications and require special care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…However, the subsequent risk of T1DM did not increase in our study. These results are consistent with those of previous studies [31][32][33]. Studies have shown that children with T1DM are more likely to develop allergic disorders (atopic rhinitis, conjunctivitis, and asthma) than the general population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the subsequent risk of T1DM did not increase in our study. These results are consistent with those of previous studies [31][32][33]. Studies have shown that children with T1DM are more likely to develop allergic disorders (atopic rhinitis, conjunctivitis, and asthma) than the general population.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that children with T1DM are more likely to develop allergic disorders (atopic rhinitis, conjunctivitis, and asthma) than the general population. Kowalczyk et al [32] measured the immunoglobulin E levels of 92 patients with T1DM and found that allergic disorders have a higher prevalence in patients with T1DM. A Turkish study showed that patients with T1DM developed more asthmatic symptoms than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The study was performed on 3 continents by Phelan et al in 2016 [6]. It is worth noting that in the Polish study of Kołodziejczyk et al body mass index in girls was also higher and indicated overweight while in boys it was normal [7]. The higher BMI in girls may by caused by multiple factors such as the influence of sex hormones on parameters of carbohydrate metabolism, low level of physical activity, and concomitance of depressive disorders in comparison to boys [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%